1550 nm Compatible Ultrafast Photoconductive Material Based on a GaAs/ErAs/GaAs Heterostructure. Issue 13 (25th April 2021) - Zhang, Kedong; Li, Yiwen; Ren, Yifeng; Fan, Xing; Li, Chen; Li, Jianfei; Meng, Yafei; Deng, Yu; Wang, Fengqiu; Lu, Hong; Chen, Yan‐Feng
Abstract: The sub‐bandgap absorption and ultrafast relaxation in a GaAs/ErAs/GaAs heterostructure are reported. The infrared absorption and 1550 nm‐excited ultrafast photo‐response are studied by Fourier transform infrared spectrometry and time‐domain pump–probe technique. The two absorption peaks located at 2.0 (0.62 eV) and 2.7 µm (0.45 eV) are originated from the ErAs/GaAs interfacial Schottky states and the ErAs itself, respectively. The photo‐excited carrier lifetime, excited using 1550 nm light, is measured to be as low as 190 fs for the GaAs/ErAs/GaAs heterostructure, making it a promising material for 1550‐nm‐technology‐compatible, high critical‐breakdown‐field THz devices. The relaxation mechanism is proposed and the functionality of ErAs is revealed. Abstract : Heterostructures composed of GaAs/ErAs/GaAs are grown by molecular beam epitaxy. Sub‐bandgap absorption in GaAs has been realized by the ErAs introduction and confirmed by Fourier transform infrared spectroscopy. Ultrafast carrier relaxation (<400 fs) is revealed using the degenerate pump–probe spectroscopy operated at 1550 nm, showing its potential applications in cost‐effective, telecom‐compatible terahertz devices.